Effect Of Additives On Zinc Silicon Carbide Composite Coating On Mild Steel By Electrodeposition - Aldhire, Tarek Mokhtar Abubaker (2019)
Zn-SiC composite coating is an effective protection measures for steel structures. Incorporation of SiC particles within zinc matrix as well as dispersion of these particles through the coating thickness are found a practical problem. In order to obtain uniform and dense Zn-SiC composite coating using electrodeposition process, operating parameters should be well controlled. Various operating parameters were used in this study. This includes current density (20, 30, 40 and 50 mA/cm2), stirring speed (300, 400, 500, 600 and 700 rpm) and SiC concentration (5, 10, 15, 20 and 25 g/L). The deposition of zinc with SiC particles was performed by electrodeposition process using zinc sulfate bath containing 2 micron sized of SiC particles. The best operating parameters obtained from preliminary study were current density of 40 mA/cm2, stirring speed of 600 rpm and SiC concentration of 20 g/L. To enhance the formation and properties of Zn-SiC composite coating, electrodeposition of Zn-SiC composite coating in presence of niobium chloride and phosphoric acid additives at various concentrations were introduced in this study. The best mechanical and corrosion properties were obtained with 10 g/L of niobium chloride and 7 g/L of phosphoric acid. The higher incorporation rate of SiC particles into zinc matrix was confirmed by SEM and EDS studies. A significant reduction in corrosion parameters of Zn-SiC composite coating was observed in which corrosion potential of -946 mv and -1008 mv were achieved with niobium chloride and phosphoric acid respectively compared with -1100 mv obtained for Zn-SiC composite coating without additives. The microhardness of the composite coating was successfully improved by using the additives during electrodeposition process. Microhardness value of 312 Hv and 252 Hv were obtained at 10 g/L of niobium chloride and 7 g/L of phosphoric acid respectively whereas it was reached to 166 Hv without additives. The change in the microstructure of Zn-SiC composite coating to fine grains was also noted. The morphology of the coating, mechanical properties and corrosion behavior of the Zn-SiC composite coating were further improved in the presence of niobium chloride and phosphoric acid additives. The presence of additives in the bath solution led to an increase in zeta potential and change the surface charge of SiC particles to more positive which results in more particles acquired to the cathode surface. Hence, the particles were more stable in the solution due to electrostatic repulsion which preventing agglomeration of these particles and consequently increase the incorporation rate of SiC in the coating.